Identifikasi Tingkat Kemampuan Berpikir Kritis Siswa pada Materi ASI Eksklusif dan Program Keluarga Berencana - Risdawaty Sinurat; Nevrita Nevrita; Nur Eka Kusuma Hindrasti (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
High school students should be able to think critically in responding to myths related to exclusive breastfeeding and family planning programs, because they are used to thinking scientifically. The purpose of this study was to determine the level of critical thinking skills of students on exclusive breastfeeding material and family planning programs in SMA Negeri I Bintan Timur. This quantitative descriptive study was conducted in the even semester of the 2018/2019 school year. The sample in this study amounted to 100 students who were determined using the Random Sampling technique. The data in this study are students' critical thinking skills. Researchers collected data using test instruments in the form of essay questions and interview rubrics. The instrument was developed based on aspects of  critical thinking, namely: (1) Basic clarification; (2) Bases for a decision; (3) Inference; (4) Advanced clarification; (5) Supposition and integration; (6) Abilities facilitate the other abilities. Furthermore, the data were analyzed using a statistical formula in the form of a percentage. Based on the results of the data analysis, it can be concluded that the critical thinking ability of the 11th grade students of Mathematics and Natural Sciences in East Negeri I Bintan is in the less category. Based on the aspect of critical thinking ability, the results obtained are aspects of basic clarification, bases for decisions, and inference in the good category, aspects of advanced clarification in the less category, while aspects of suppositionand integration and the abilities to facilitate other abilities in the middle category